Math, asked by HarshadTambvekar, 4 months ago

please solve this , what is after last step​

Attachments:

Answers

Answered by gopalpvr
1

Answer:

12x-y= 66 is required equation

Step-by-step explanation:

y- 6= (x-6) 12

y-6= x×12-6×12

y-6= 12x-72

y-12x= 6-72

y-12x=-66

multiply with -1 on both sides

-1×y -(-1) ×12x= -1×-66

-y+12x= 66

12x-y= 66 is required equation

Answered by pdineshd11
1

Answer:

x=7

y=18

Step-by-step explanation:

-2x+y=4(1)

12x-y=66(2)

by adding these two equations, we get

10x=70

x=7

put x value in equation

-2(7) +y=4

y=18

Similar questions